Weathering the storm: a descriptive examination of COVID era proficiency changes in charter schools - Kingsbury, Ian (Frontiers in Education, 2024)
The COVID-19 pandemic imposed unprecedented disruptions on American education and contributed to profound learning loss. The stakes attached to learning loss are especially high for charter schools, whose survival and potential expansion or replication is heavily tied to test score performance. Using nationwide school-level proficiency data, this study examines achievement patterns in the charter sector between 2018-19 and 2020-21. Overall, it emerges that school proficiency rates in 2018-19 remained strongly predictive of proficiency rates in 2020-21. Still, certain notable patterns emerge from the data. Charters that serve more Black, Hispanic, and economically disadvantaged students lost more ground. Moreover, charters affiliated with education management organizations experienced less learning loss than other types of charter schools.